Towards Participatory MOOCs - Amit, Pariyar; Narayanan, Kulathuramaiyer; Poline, Bala (Routledge, 2020)
This chapter presents a uniqueperspective on the participatory role of marginalized community in the knowledge exchange with our “Community Led MOOCs”by showcasing their ability tofoster knowledge creation from the ground, and contribute in bridging theglobal local knowledge divide. Thenovel case of participatory MOOCs with single mother communities in Bario, a remote and rural region in the Borneo Island of Malaysia, redefines‘inclusive’ and ‘participatory’ nature of learning by integrating communityparticipation, their learning context and way of life. The outcome is a MOOC module on “Threading Beads” which represents the cultural knowledge preservation effort by the rural single mothers forfuture generations.